2019
DOI: 10.1039/c9sc04387j
|View full text |Cite
|
Sign up to set email alerts
|

Self-triggered click reaction in an Alzheimer's disease model:in situbifunctional drug synthesis catalyzed by neurotoxic copper accumulated in amyloid-β plaques

Abstract: Accumulated Cu in amyloid-β plaques can effectively catalyze the azide–alkyne cycloaddition reaction for fluorophore activation and drug synthesis. Our work may provide new insight intoin situdrug synthesis for neurodegenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 86 publications
(96 reference statements)
1
42
0
Order By: Relevance
“…9,10 To solve these problems, in situ syntheses of highly toxic anticancer drugs from non-toxic agents triggered by diverse articially delivered nanoparticles in the TME have aroused great interest. [11][12][13][14][15][16][17] Such a strategy would make the therapeutic process occur in only the tumor tissue without toxicity to normal tissues, so as to achieve high therapeutic efficacy while minimizing damage to normal tissues and/or organs. Unfortunately, the ultralow yields of toxic drugs have impeded their curative chemotherapy effect, limiting their further applications.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 To solve these problems, in situ syntheses of highly toxic anticancer drugs from non-toxic agents triggered by diverse articially delivered nanoparticles in the TME have aroused great interest. [11][12][13][14][15][16][17] Such a strategy would make the therapeutic process occur in only the tumor tissue without toxicity to normal tissues, so as to achieve high therapeutic efficacy while minimizing damage to normal tissues and/or organs. Unfortunately, the ultralow yields of toxic drugs have impeded their curative chemotherapy effect, limiting their further applications.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has demonstrated that neurotoxic copper accumulated in Aβ plaques could effectively catalyze an azide–alkyne biorthogonal cycloaddition reaction when Cu-Aβ aggregates were used as the catalysts. 31 Indeed, the fluorescence intensity of the click reaction increased about 20-fold after 10 minutes of reaction (Fig. S14 † ).…”
Section: Resultsmentioning
confidence: 97%
“…Notably, the typical concentration of Cu is 0.4 mM in Aβ plaques, which is enough for catalyzing CuAAC. 31 As artificial Aβ-receptors on the microglial membrane, ThS could capture extracellular Aβ aggregates and improve the ability of microglia to phagocytose Aβ through receptor-mediated endocytosis (RME). To circumvent the over-activation of microglia during the process of the click reaction and Aβ phagocytosis, the manganese porphyrin linkers in the Mn-MOF carrier would mimic the function of natural SOD and CAT to shift microglial phenotypic transition to the neuroprotective subtype through regulating redox equilibrium ( Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The AD transgenic strain C. elegans CL2006, a widely used AD model, is characterized by Ab peptides expressed in muscle cells. 52 Thioavin S (ThS) staining was performed to evaluate the effect of PKNPs on the Ab deposits in the CL2006 worms ( Fig. 4b-e).…”
Section: Resultsmentioning
confidence: 99%